Activation and Purification of ß-Glucocerebrosidase by Exploiting its Transporter LIMP-2 – Implications for Novel Treatment Strategies in Gaucher's and Parkinson's Disease - Dobert, Jan; Bub, Simon; Mächtel, Rebecca; Januliene, Dovile; Steger, Lisa; Regensburger, Martin; Wilfling, Sibylle; Chen, Jia Xuan; Dejung, Mario; Plötz, Sonja; Hehr, Ute; Moeller, Arne; et al. (Advanced Science, 2024)
Genetic variants of GBA1 can cause the lysosomal storage disorder Gaucher disease and are among the highest genetic risk factors for Parkinson's disease (PD). GBA1 encodes the lysosomal enzyme beta-glucocerebrosidase (GCase), which orchestrates the degradation of glucosylceramide (GluCer) in the lysosome. Recent studies have shown that GluCer accelerates α-synuclein aggregation, exposing GCase deficiency as a major risk factor in PD pathology and as a promising target for treatment. This study investigates the interaction of GCase and three disease-associated variants (p.E326K, p.N370S, p.L444P) with their transporter, the lysosomal integral membrane protein 2 (LIMP-2). Overexpression of LIMP-2 in HEK 293T cells boosts lysosomal abundance of wt, E326K, and N370S GCase and increases/rescues enzymatic activity of the wt and E326K variant. Using a novel purification approach, co-purification of untagged wt, E326K, and N370S GCase in complex with His-tagged LIMP-2 from cell supernatant of HEK 293F cells is achieved, confirming functional binding and trafficking for these variants. Furthermore, a single helix in the LIMP-2 ectodomain is exploited to design a lysosome-targeted peptide that enhances lysosomal GCase activity in PD patient-derived and control fibroblasts. These findings reveal LIMP-2 as an allosteric activator of GCase, suggesting a possible therapeutic potential of targeting this interaction.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Gaucher's disease (GD); GCase; LIMP-2; lysosomes; Parkinson's disease (PD); protein purification; β-glucocerebrosidase

From Lysosomal Storage Disorders to Parkinson's Disease – Challenges and Opportunities - Mächtel, Rebecca; Boros, Fanni Annamaria; Dobert, Jan; Arnold, Philipp; Zunke, Friederike (Journal of Molecular Biology, 2023)
Lysosomes are specialized organelles with an acidic pH that act as recycling hubs for intracellular and extracellular components. They harbour numerous different hydrolytic enzymes to degrade substrates like proteins, peptides, and glycolipids. Reduced catalytic activity of lysosomal enzymes can cause the accumulation of these substrates and loss of lysosomal integrity, resulting in lysosomal dysfunction and lysosomal storage disorders (LSDs). Post-mitotic cells, such as neurons, seem to be highly sensitive to damages induced by lysosomal dysfunction, thus LSDs often manifest with neurological symptoms. Interestingly, some LSDs and Parkinson's disease (PD) share common cellular pathomechanisms, suggesting convergence of aetiology of the two disease types. This is further underlined by genetic associations of several lysosomal genes involved in LSDs with PD. The increasing number of lysosome-associated genetic risk factors for PD makes it necessary to understand functions and interactions of lysosomal proteins/enzymes both in health and disease, thereby holding the potential to identify new therapeutic targets. In this review, we highlight genetic and mechanistic interactions between the complex lysosomal network, LSDs and PD, and elaborate on methodical challenges in lysosomal research.
CRIS-Team Scopus Importer:2023-03-24
Keywords: lysosomal enzymes; lysosomal storage disorder; lysosome; neurodegeneration; Parkinson's disease

Late-onset Krabbe disease presenting as spastic paraplegia – implications of GCase and CTSB/D - Mächtel, Rebecca; Dobert, Jan; Hehr, Ute; Weiß, Alexander; Kettwig, Matthias; Laugwitz, Lucia; Groeschel, Samuel; Schmidt, Manuel; Arnold, Philipp; Regensburger, Martin; Zunke, Friederike (Annals of Clinical and Translational Neurology, 2024)
Objective: Krabbe disease (KD) is a multisystem neurodegenerative disorder with severe disability and premature death, mostly with an infancy/childhood onset. In rare cases of late-onset phenotypes, symptoms are often milder and difficult to diagnose. We here present a translational approach combining diagnostic and biochemical analyses of a male patient with a progressive gait disorder starting at the age of 44 years, with a final diagnosis of late-onset KD (LOKD). Methods: Additionally to cerebral MRI, protein structural analyses of the β-galactocerebrosidase protein (GALC) were performed. Moreover, expression, lysosomal localization, and activities of β-glucocerebrosidase (GCase), cathepsin B (CTSB), and cathepsin D (CTSD) were analyzed in leukocytes, fibroblasts, and lysosomes of fibroblasts. Results: Exome sequencing revealed biallelic likely pathogenic variants: GALC exons 11–17: 33 kb deletion; exon 4: missense variant (c.334A>G, p.Thr112Ala). We detected a reduced GALC activity in leukocytes and fibroblasts. While histological KD phenotypes were absent in fibroblasts, they showed a significantly decreased activities of GCase, CTSB, and CTSD in lysosomal fractions, while expression levels were unaffected. Interpretation: The presented LOKD case underlines the age-dependent appearance of a mildly pathogenic GALC variant and its interplay with other lysosomal proteins. As GALC malfunction results in reduced ceramide levels, we assume this to be causative for the here described decrease in CTSB and CTSD activity, potentially leading to diminished GCase activity. Hence, we emphasize the importance of a functional interplay between the lysosomal enzymes GALC, CTSB, CTSD, and GCase, as well as between their substrates, and propose their conjoined contribution in KD pathology.
CRIS-Team Scopus Importer:2024-06-14
Keywords: cathepsin B; cathepsin D; enzymatic activity; Krabbe disease; late-onset; β-glucocerebrosidase